SUPERVISI PENDIDIKAN ISLAM: INTEGRASI ETIKA ISLAMI DAN PROFESIONALISME DALAM PENINGKATAN MUTU PENDIDIKAN ISLAM - Misda Ariyani (PT. Hasba Edukasi Mandiri, 2026)
This study aims to examine the model of Islamic education supervision, analyse the role of supervisors in integrating Islamic ethics and professionalism in education supervision, understand the implications of Islamic education supervision in the context of improving education quality, and compare it with previous relevant studies. The approach used is library research with data collection techniques in the form of documentation studies of books, accredited national and international journal articles, and relevant Islamic sources. The data were analysed using content analysis techniques through a process of data reduction, data presentation, and systematic conclusion drawing. The results of the study show that: 1) The Islamic education supervision model is understood as a coaching process that balances the assessment of educators' performance with the strengthening of moral, spiritual, and ethical aspects in accordance with Islamic values. 2) The relationship between Islamic ethics and professionalism is inseparable, because both form a unity that represents the ideal character of an educator. 3) The implication of this supervision model is an increase in the quality of Islamic education, marked by the growth of an educational environment that upholds knowledge, manners, sincerity, and exemplary behaviour. 4) This study positions Islamic education supervision as a conceptual and normative study that emphasises the holistic integration of Islamic ethics and professionalism. The conclusion of the study affirms that Islamic education supervision plays a strategic role in improving the quality of education through the formation of professional and ethical educators.